Algerian Youth and the Contestation over Sound on TikTok. Issue 2 (1st January 2023) - Bruls, Luca
Abstract: In Algeria, youth form attitudes towards music as a result of their TikTok usage. The responses of governmental institutions, Facebook users, and middle‐class TikTokers to popular raï songs unfold the contestation over sound. Drawing on nethnography, I expose the moralizing and politicized responses that couple these different groups in their criticism. Through an account of the conversations and interactions with middle‐class Algerian youth, I demonstrate TikTok's subdivision into two opposed, yet interdependent scenes. The text draws on examples of the engagement between the two groups to reveal how youth call attention to their class identities by listening and sounding, as well as related expressions of dancing and dressing. The friendships and engagements online are a result of youth's scaling practices in TikTok's For You algorithm. Through their negotiation of songs, performances, and humour, middle‐class youth create a sonic class line that separates them from vulnerable classes. The moralizing stories that these middle‐class youth tell are an everyday representation of the different classes in Algeria. Studying sound on TikTok can help ethnographers learn about the concomitant memes and stereotypes that circulate online.